Change at home, in the labor market, and on the job - Polachek, Solomon W.; Tatsiramos, Konstantinos (Emerald Publishing Limited, 2020)
How do changes at home, in the labor market and on the job affect worker well-being? This volume of Research in Labor Economics contains eight original and insightful articles answering this question. Seven deal with demographic and labor market change, and one deals with wage differences essentially at a point in time. Of the seven, two articles analyze changes in family related matters and have implications regarding labor supply; two examine legislative changes, one of which has implications on teenage employment, and the other on informal business formation; one looks at potential productivity changes on farms in a developing country and has implications for remaining on the family farm or going to work; one models wage growth and shows why wages sometimes fall as one remains in a job longer; and finally, one investigates new enterprise formation over time.
Chapter 1: Educational Homogamy and Assortative Mating Have Not Increased; Rania Gihleb and Kevin Lang -- Chapter 2: The Long-term Impact of Work-Hour Regulations on Physician Labor Supply; Judith Liu -- Chapter 3: Rural Shadow Wages and Youth Agricultural Labor Supply in Ethiopia: Evidence from Farm Panel Data; Tekalign Gutu Sakketa and Nicolas Gerber -- Chapter 4: Minimum Wage Effects: Empirical Evidence from Japan; Masao Yamaguchi -- Chapter 5: Payroll Taxes, Social Security and Informality: The 2012 Tax Reform in Colombia; Pablo Adrian Garlati-Bertoldi -- Chapter 6: The Age Pay Gap Between Young and Older Employees in Italy: Perceived or Real Discrimination against the Young? Carolina Castagnetti, Luisa Rosti, and Marina Töpfer -- Chapter 7: Non-Promotion Signals and Job Tenure: Theory and Evidence; Xin Jin -- Chapter 8: Defining Opportunity Versus Necessity Entrepreneurship: Two Components of Business Creation; Robert W. Fairlie and Frank M. Fossen.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Labor market; Business & Economics -- Labor; Employment & unemployment